2021
DOI: 10.1037/pag0000642
|View full text |Cite
|
Sign up to set email alerts
|

Does early-stage intervention improve caregiver well-being or their ability to provide care to persons with mild dementia or mild cognitive impairment? A systematic review and meta-analysis.

Abstract: Interventions for caregivers of persons with dementia are well supported, but it remains unclear whether caregivers benefit from early-stage intervention when caring for persons with mild dementia or mild cognitive impairment (MCI). This systematic review and meta-analysis examined whether early-stage interventions for this population positively affect their well-being and ability to provide care and whether effectiveness varies based on intervention or caregiver/recipient characteristics. Searches of four dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 70 publications
1
6
0
Order By: Relevance
“…The mediation analysis supported the idea that positive feeling had a positive effect on HRQoL through caring ability. Our study showed that positive feeling was positively associated with caring ability, which was in line with of previous study ( Cheng et al, 2019 ; Bayly et al, 2021 ; Li-li et al, 2021 ). Caregivers with a higher level of positive feelings were better at realizing their personal values.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The mediation analysis supported the idea that positive feeling had a positive effect on HRQoL through caring ability. Our study showed that positive feeling was positively associated with caring ability, which was in line with of previous study ( Cheng et al, 2019 ; Bayly et al, 2021 ; Li-li et al, 2021 ). Caregivers with a higher level of positive feelings were better at realizing their personal values.…”
Section: Discussionsupporting
confidence: 93%
“…Previous study showed that a sense of gratification was felt when family caregivers were satisfied with their efforts in improving the wellbeing and functional status of the patients with dementia ( Yu et al, 2018 ). The positive feelings of caregivers were associated with stronger caring ability and longer caring time, which help improve wellbeing of patients with dementia and stroke ( Skolarus et al, 2017 ; Bayly et al, 2021 ). However, literatures on the relationships between caregivers’ positive feelings and IBD-related HRQoL were relatively lacking.…”
Section: Introductionmentioning
confidence: 99%
“…With regard to the participants, findings of the subgroup analysis indicated that multi-component interventions recruiting caregivers only might have a better effect than dyadic interventions in terms of depression and burden. One possible reason is that intervention contents are mainly developed for caregivers [ 57 ], and caregivers can temporarily leave the caring environment and receive a short respite [ 25 ]. More detailed information about the intervention content and implementation strategies are required for exploring the best combination of intervention content and dosage in multi-component interventions.…”
Section: Discussionmentioning
confidence: 99%
“…This study showed a significantly increasing trend in the prevalence of registered dementia cases and of registered multimorbidity (3+ comorbidities) in dementia patients over from 2000 to 2021 [ 6 ]. Providing early support for informal caregivers can improve their wellbeing and ability to care, keeping older people with cognitive decline at home longer and diminishing public healthcare costs [ 7 11 ]. However, scientific literature has shown that very few psychosocial interventions target informal caregivers at the early stage of caregiving [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%